2011
DOI: 10.1614/ipsm-d-10-00054.1
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating Downy Brome (Bromus tectorum)–Invaded Shrublands Using Imazapic and Seeding with Native Shrubs

Abstract: Rehabilitation of downy brome–infested shrublands is challenging once this invasive grass dominates native communities. The effectiveness of imazapic herbicide in reducing downy brome cover has been variable, and there is uncertainty about the impacts of imazapic on native species. We used a before-after-control-impact (BACI) field experiment and greenhouse studies to (1) determine if imazapic herbicide applied at 132 g ai ha−1 (8 oz/ac−1) and seeding with two native shrub species (Wyoming big sagebrush [Artem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
2
26
1
Order By: Relevance
“…The most noteworthy exception to that was in the POST treatment, where 70 g ai ha 21 resulted in lower control than did the other rates. Our results are consistent with label recommendations of 105 to 211 g ai ha 21 (Anonymous 2008) and those from other studies (Baker et al 2009;Davison and Smith 2007;Elseroad and Rudd 2011;Owen et al 2011). Downy brome control may increase with increasing imazapic application rate (Morris et al 2009), but high rates can also increase the risk of injury to Figure 1.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The most noteworthy exception to that was in the POST treatment, where 70 g ai ha 21 resulted in lower control than did the other rates. Our results are consistent with label recommendations of 105 to 211 g ai ha 21 (Anonymous 2008) and those from other studies (Baker et al 2009;Davison and Smith 2007;Elseroad and Rudd 2011;Owen et al 2011). Downy brome control may increase with increasing imazapic application rate (Morris et al 2009), but high rates can also increase the risk of injury to Figure 1.…”
Section: Resultssupporting
confidence: 91%
“…In reviewing the literature, we found one study that addressed downy brome growth stage at the time of imazapic application. In this greenhouse study, imazapic was applied at 132 g ai ha 21 to downy brome seeds, to plants with two to four leaves, and to plants with 5 to 10 leaves (Owen et al 2011). Downy brome mortality was 90 and 100% after imazapic treatment, regardless of timing of application; however, results from the greenhouse study contradicted results from a companion field study where growth stage was not reported (Owen et al 2011).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Of those five, two found at least mixed support for woody revegetation suppressing IPS. Cabin, Weller, Lorence, Cordell, and Hadway () found planting and seeding native Hawai'ian woody species increased understorey cover and reduced invasion of the grass Pennisetum setaceum (Fountain grass), whereas Owen, Sieg, and Gehring () found seeding native shrubs to be ineffective at suppressing the grass Bromus tectorum (Cheatgrass). Notably, Knutson et al.…”
Section: Revegetation To Suppress Invasion: Evidencementioning
confidence: 99%
“…However, other studies from semiarid climates resulted in only 1 yr of control over downy brome and other invasive annual grasses. For example, Owen et al (2011) reported that imazapic applied at 132 g ha À1 in the late fall reduced downy brome cover and biomass during the first season after application but had no effect during the second season. Similarly, Sheley et al (2007) found that medusahead [Taeniatherum caput-medusae (L.) Nevski] in eastern Oregon was effectively controlled by imazapic (!…”
Section: Resultsmentioning
confidence: 99%